Some notes on Pamijahans’ Manuscripts - T. Christomy, (Universiti Kebangsaan Malaysia, 2007)
Pamijahan is a small village in the southern part of the regency (kabupaten) of Tasikmalaya in the Priangan Timur area of West Java. This village is very important in the history of Shattariyah in Java. Today, it is a popular site for pilgrims visiting the tomb of Shaykh Abd al-Muhyi, the ancestor of the Pamijahanese and the propagator of Shattariyah. This article explores some manuscripts related to Shaykh Abd al-Muhyi found in this area